1980
DOI: 10.1111/j.1365-2133.1980.tb08142.x
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled DNA synthesis in psoriatic skin after ultraviolet irradiation and the effects of a combined treatment with 8-methoxypsoralen and longwave ultraviolet radiation: a clinical study*

Abstract: Biopsies were taken from psoriatic patients undergoing photochemotherapy and then studied by autoradiography to investigate possible unscheduled DNA synthesis (UDS) following 8-MOP photodamage in epidermal cels. No sparse labelling was found in seventy samples taken from twenty-four different patients during PUVA therapy, indicating a lack of UDS. In contrast, UDS was observed in three patients irradiated with an all-spectrum UV lamp, as a test for DNA damage and excision repair activity. The incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…Thus, the induction of UDS by PUVA was far smaller than that by 4-nitroquinoline 1-oxide (4NQO), N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) or UV-B irradiation (Mori et al, 1999(Mori et al, , 2000a. In studies in vivo or in vivo -in vitro by an autoradiographic method, previous investigators have failed to detect induction of UDS (Epstein and Fukuyama, 1975;Bioulac et al, 1980;Hönigsmann et al, 1981;Bishop and Abel, 1985). Our success in the detection of UDS induction in vivo -in vitro in the present study might have been due to the carefully designed experimental procedures that we employed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, the induction of UDS by PUVA was far smaller than that by 4-nitroquinoline 1-oxide (4NQO), N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) or UV-B irradiation (Mori et al, 1999(Mori et al, , 2000a. In studies in vivo or in vivo -in vitro by an autoradiographic method, previous investigators have failed to detect induction of UDS (Epstein and Fukuyama, 1975;Bioulac et al, 1980;Hönigsmann et al, 1981;Bishop and Abel, 1985). Our success in the detection of UDS induction in vivo -in vitro in the present study might have been due to the carefully designed experimental procedures that we employed.…”
Section: Discussionmentioning
confidence: 94%
“…For example, we used a UV-absorbing glass filter in order to eliminate the wavelength range of UV-B. In other studies, a UV-absorbing glass filter was not used (Bioulac et al, 1980), or a plate glass with a low UV-absorbing effect was used (Bishop and Abel, 1985). The presence of UV-B would increase the control level of DNA synthesis, and thereby mask slight induction of UDS by PUVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo in man, the mechanism of the antipro liferative action of PUVA therapy in the remission of psoriasis is not yet clear, al though in vitro studies have shown that the major cytotoxic effect due to psoralens and UVA light occurs via the inhibition of semi conservative DNA synthesis. In fact, despite the numerous in vivo reports on animals [14,34,35] and also in psoriatic patients [12,13], DNA synthesis inhibition as well as DNA repair synthesis [36][37][38][39] have not been un equivocally demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing angelicin to 8-MOP, it was found that much higher concentrations of angelicin were necessary to photo-suppress DNA synthesis [30,40]. Unscheduled DNA synthesis, which appears to represent DNA damage and excision repair activity, was lacking in skin samples taken from patients during PUVA therapy [4]. This was compared to the skin of patients irradiated with an all-spectrum UV light in whom unscheduled DNA synthesis was observed.…”
Section: -Methoxypsoralen(8-mop)mentioning
confidence: 99%